(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, a sociolinguistic approach to units of reference in the Uzbek and Russian languages is reflected. Such views are ultimately important for understanding the unique features of national communication styles, language and culture, politeness strategies, as well as for increasing cultural communicative competence when communicating in a foreign language.